Case report: Pathological complete response to perioperative treatment of radiotherapy combined with angiogenesis inhibitor in a patient with pleomorphic liposarcoma - Zhang, Chenlu; Liu, Wenshuai; Wang, Binliang; Zhu, Na; Guo, Xi; Wang, Zhiming; Zhuang, Rongyuan; You, Yang; Zhang, Yong; Tong, Hanxing; Lu, Weiqi; Zhou, Yuhong (Frontiers in Oncology, 2023)
Background: Liposarcomas (LPS) are mesenchymal malignancies with four principal subtypes presenting distinct molecular and clinical features. Pleomorphic liposarcoma (PLPS) is one of the rarest and the most aggressive subtypes of LPS. Surgical resection is currently a preferred curative approach to localized PLPS. However, the prognosis of unresectable PLPS is very poor and there is no standard treatment for it. Case presentation: A 59-year-old Chinese woman was diagnosed as unresectable PLPS. The case was discussed and managed by specialists of multidisciplinary team in Fudan Zhongshan Hospital. Preoperative radiotherapy (RT) of intensity-modulated radiation therapy (IMRT) at 50Gy/25Fx concurrently with angiogenesis inhibitor anlotinib (8 mg, day 1-14, every 3 week) were prescribed to the patient. The dosage of anlotinib was increased to 10 mg after RT. After 6 months of treatment, the tumor was significantly shrunk and successfully resected. The exam of surgical specimens showed pathological complete response (pCR). Until the latest follow-up (April, 2022), no recurrence was observed and disease free survival has exceeded 14 months. Conclusion: The case presented shed light on the probability that perioperative RT combined with angiogenesis inhibitor can be effectively used in PLPS which is resistance to chemotherapy and usually considered poor prognosis. Further studies with randomly controlled clinical trials will improve our knowledge of this preoperative treatment strategy.